Legal Analysis of the Implementation of Criminal Sanctions in the Crime of Togel Gambling: Study of Court Decision Number 420/PID.B/2021/PN.SIM - Sarles Gultom; Van Lodewijk Purba; Simeun Petrus Saragih (KOLABORASI: Journal of Multidisciplinary, 2025)
The rampant practice of lottery gambling in society reflects a failure in building public rationality that causes life to become more speculative, marked by uncertainty, instant mindsets, and dependence on luck through numbers, which ultimately erodes the values of hard work and discipline, while this study attempts to answer several main problem formulations, namely the factors that encourage someone to gamble on the lottery, the impacts caused to society, and how criminal responsibility is imposed on lottery gamblers, where this study uses a library research method (Library Research) by examining various legal sources such as laws and regulations, legal theories, court decisions, and expert opinions in order to find solutions to existing problems, so that it is concluded that the main factors that encourage lottery gamblers include gambling as a hobby, filling free time, environmental influences, and efforts to improve the economy, while the impacts of this gambling are very broad, including increased crime rates, financial problems, health problems, wasting time, wasting resources, social losses, wasting opportunities, and potential corruption, and based on the facts revealed in court, the Public Prosecutor charged the defendant with alternative charges based on Article 303 Paragraph (1) 1 and Article 303 Paragraph (1) 2 of the Criminal Code, so that the defendant can be held criminally responsible as regulated in Article 303 Paragraph (1) 2 of the Criminal Code in the Second Indictment.